PENGARUH IMPLEMENTASI KEBIJAKAN SISTEM INFORMASI PEMERINTAHAN DAERAH TERHADAP MANAJEMEN DATA DAN INFORMASI PEMBANGUNAN DI KABUPATEN SUMEDANG - Asyaroh, Siti (JRPA - Journal of Regional Public Administration, 2024)
This research aims to examine and analyze the influence of implementing regional development information system policies on regional development data and information management,The research method used is a descriptive analysis method using survey techniques, with research variables consisting of the independent variable, namely Implementation of Regional Development Information System Policy, and the dependent variable, namely Data Management and Development Information. The research population was 30 people, consisting of all regional apparatus within the Sumedang Regency government. The sampling technique used a saturated sample or census, that is, the entire research population was used as respondents in the research. Data collection techniques were carried out using documentation studies and field studies through the distribution of questionnaires.The technical data analysis carried out in this research is a path analysis model (Path Analysis). The results of testing the main hypothesis show that the implementation of Regional Development Information System Policy (X) has an influence on Development Data and Information Management (Y). The influence of regional development information system policy implementation (X) on development data and information management (Y) is 46.2%. Suggestions for improving problems in implementing regional development information system policies are that improvements to the bureaucratic structure still require improvement, especially for SOPs for policy implementation that need to be prepared/established, apart from that the data also shows that it is still necessary to clarify the division of tasks and functions. As for Data and Information Management that needs to be improved, it is in the dimension of Mobilizing Data Management and Development Information, especially in the issue of providing incentives and disincentives from leaders to data managers